Recommendations of the Polish Dental Association and the Polish Medical Society of Radiology Working Group regarding taking dental radiographs during the pandemic of COVID-19 - Różyło-Kalinowska, Ingrid; Dominiak, Marzena; Cieszanowski, Andrzej; Kulczyk, Tomasz (Journal of Stomatology, 2020)
1. In SARS-CoV-2-positive patients diagnosed with PCR tests and in persons under quarantine, all dental radiographs should be taken only in facilities, which are specifically dedicated to treatment of COVID-19 patients, such as infectious diseases hospitals, hospitals with infectious diseases wards, and special dental offices or mobile dental offices (“dentobus”) designated to provide services to these patients [1, 2].